2021
DOI: 10.33403/rigeo.799602
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cooperative Letters and Cooperative Posters on the Academic Achievements of Social Studies Teacher Candidates

Abstract: The aim of this study is to investigate the effect of cooperative letter and cooperative poster studies on the academic achievement of social studies teacher candidates in contemporary world history course and the relationship between learning writing and course success. In the research, quantitative model was adopted and quasi-experimental design with pretest-posttest comparison groups was used. The study group of the research consists of 78 social studies teacher candidates studying at Atatürk University in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In another scenario, it has been reported that though many students complain because they have to design a poster, they also have read more for their presentation and this motivates them because they learned more (Kinikin & Hench, 2012). Likewise, the fact that posters allow students and teachers to discuss and analyze their posters as the final product, allows for sharing ideas, or to correct mistakes, or simply transfer more knowledge collaboratively (Akdağ & Yildiz, 2021). It is understood that any process for learning to write has certain conditions like the student"s English level, the editing process made by students with help from the teacher, take into account recommendations like paraphrasing and avoiding plagiarism, and all of them can be developed through posters (Maki Haffa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In another scenario, it has been reported that though many students complain because they have to design a poster, they also have read more for their presentation and this motivates them because they learned more (Kinikin & Hench, 2012). Likewise, the fact that posters allow students and teachers to discuss and analyze their posters as the final product, allows for sharing ideas, or to correct mistakes, or simply transfer more knowledge collaboratively (Akdağ & Yildiz, 2021). It is understood that any process for learning to write has certain conditions like the student"s English level, the editing process made by students with help from the teacher, take into account recommendations like paraphrasing and avoiding plagiarism, and all of them can be developed through posters (Maki Haffa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%